The nature of s-process nucleosynthesis in low mass AGB stars based on individual Barium star observations. (October 2020) - Cseh, B; Vil´agos, B; Lugaro, M; D'Orazi, V; Karakas, A I; Pereira, C B
Abstract: Barium stars are now primaries in a binary system with a former asymptotic giant branch (AGB) star. Here we compare some available AGB nucleosynthesis models and the observed s-process abundances of individual Ba star measurements to constrain the nature of the s-process in low mass AGB stars. After correcting the models with a dilution factor calculated for [Ce/Fe], we found that some of the sample stars show higher abundances for light s-process elements than the model predictions. This might be attributed to diffusive mixing in the stars.